The Cut-off Value of Great Saphenous Vein Diameter at the Level of Femoral Condyle to Predict the Sapheno-Femoral Junction Incompetence - Singh, A. K.; Karmacharya, R. M.; Vaidya, S.; Shrestha, I.; Siwakoti, S. (Kathmandu University Medical Journal, 2022)
Background Varicose vein is one of the commonest problems that patients visit to a vascular out patient services (OPD). It causes a great deal of morbidity in today’s population. Objective To see the correlation between the size of great saphenous and Saphenofemoral junction incompetence. Method From January 2019 till January 2020, 396 patients with symptomatic or clinically diagnosed varicose veins were screened for Saphenofemoral junction reflux. The diameter of the saphenous vein was measured with B-mode imaging, and reflux was quantified based on valve closure time using Doppler spectral measurements. Best saphenous vein diameter cutoff for predicting reflux was determined using receiver operating characteristics curve analysis. Result Out of 792 limbs, the Great Saphenous Venous System was involved in 452 limbs, the Short Saphenous Venous System was involved in 151 limbs and significant perforators were present in 240 limbs. Mean great Saphenous Vein diameter of diseased limb (Reflux Positive) was 5.68 mm and 4.0 mm in control group (Reflux Negative). Mean Saphenofemoral junction diameter was 8.23 mm in diseased limbs and 6.16 mm in control limbs. Receiver operating characteristics curve showed great saphenous vein diameter at femoral condyle of 4.5 mm as best cut-off value for diagnosis of sapheno femoral junction reflux. Conclusion Great Saphenous Vein diameter at femoral condyle of 4.5 mm is the best cut-off value for diagnosis Saphenofemoral junction reflux. The Sensitivity and specificity of this cut off value is 81.8% and 71% respectively.